Analisis Kontribusi Pajak Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah - Trisnasari, Regina; Sunaningsih, Suci Nasehati (Universitas Gorontalo, 2022)
This study describes the contribution of the local taxes and levies on revenue. The research objectives are: (1) to determine the growth rate of Regional Taxes and Regional Levies; (2) to determine the contribution of Regional Tax revenue; and (3) to determine the contribution of Regional Levies revenue. The method used in this research is descriptive research. The data that used in this research is secondary data or data that has been published in the form of Realization of Revenue from Magelang Regency in 2015-2020 obtained from the Regional Revenue, Financial and Asset Management Agency of Magelang Regency. In this research, the researcher uses the analysis of growth and contribution. The results showed that local taxes and levies have a contribution to local revenue with an average growth of taxes and levies in Magelang Regency during 2015-2020 which is quite potential. Meanwhile, the average tax contribution in Magelang Regency in 2015-2020 was 34.4% including the sufficient category and the average contribution of regional levies in 2015-2020 was 6.56%. categorized as very low.